Childhood cancer in children with congenital anomalies in Oklahoma, 1997 to 2009. Issue 7 (4th March 2016) - Janitz, Amanda E.; Neas, Barbara R.; Campbell, Janis E.; Pate, Anne E.; Stoner, Julie A.; Magzamen, Sheryl L.; Peck, Jennifer D.
Abstract : Background: Data‐linkage studies have reported an association between congenital anomalies and childhood cancer. However, few studies have focused on the differences in the effect of congenital anomalies on cancer as a function of attained age. We aimed to examine associations between anomalies and childhood cancer as a function of attained age among children born in Oklahoma. Methods: Data were obtained from the Oklahoma State Department of Health from 1997 to 2009 ( n = 591, 235). We linked Vital Statistics records for singleton deliveries to the Oklahoma Birth Defects Registry and the Oklahoma Central Cancer Registry using name and birth date. To assess the relation between anomalies and childhood cancer, we used Cox regression analysis allowing for a nonproportional hazards for anomalies as a function of age. Results: There were 23, 368 (4.0%) children with anomalies and 531 (0.1%) children with cancer. When considering 3‐year age intervals, we detected an increased hazard of any childhood cancer in children with anomalies compared with those without anomalies before 1 year of age (hazard ratio, 14.1; 95% confidence interval, 8.3–23.7) and at 3 years of age (hazard ratio, 2.3; 95% confidence interval, 1.6–3.2). The increased hazard declined with increasing time since birth, with the effect diminished by 6 years of age. Conclusion: Our results were consistent with previous studies indicating an increased rate of childhood cancer among children with anomalies at younger ages. Furthermore, our study added a methodological refinement of assessing the effect of anomalies as a function of attained age. Birth Defects Research (Part A) 106:633–642, 2016. © 2016 Wiley Periodicals, Inc.